Handbook of experimental economics results - Plott, Charles R.; Smith, Vernon L. (Handbooks in economics, 2008)
Experimental methods in economics respond to circumstances that are not completely dictated by accepted theory or outstanding problems. While the field of economics makes sharp distinctions and produces precise theory, the work of experimental economics sometimes appear blurred and may produce results that vary from strong support to little or partial support of the relevant theory. At a recent conference, a question was asked about where experimental methods might be more useful than field methods. Although many cannot be answered by experimental methods, there are questions that can only